S07-1: Promoting Physical Literacy in Higher Education Physical Education: ePhyLi (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The ePhyLi project, funded by the Erasmus+ Sport Programme (No. 101089928), aims to promote awareness and activity in health-enhancing physical activity (HEPA) environments and the adoption of a healthy lifestyle, addressing priority areas of the EU work plan for sport. This will be achieved by: (1) increasing the knowledge and understanding about the notion of physical literacy (PL) of university students who study physical education (PE), sport and exercise science, (2) properly preparing them for further promoting PL to their students, as part of their future teaching career, becoming PL advocators.Project Description: The project is implemented collaboratively by five partners across four European countries: Cyprus, Italy, France, and EU-wide with the support of EUPEA. The main target group consists of university students studying to become PE and school teachers, as well as pre-service and in-service PE teachers. Stakeholders involved included university educators, digital learning experts, and sport education professionals. Implementation involved the creation of three main outputs: (1) an e-book, featuring eight structured modules and available in four languages (English, Greek, Italian, and French); (2) the ePhyLi serious game, a mobile application reinforcing PL concepts through interactive gameplay; (3) an e-platform offering gamified learning units, educational comic books, and interactive activities. The project is currently undergoing its second pilot phase, implemented by all partners. This phase includes structured testing of both the e-learning platform and the app with university students and relevant stakeholders. Evaluation activities focus on assessing the tools’ effectiveness in enhancing participants’ understanding of PL, as well as their usability, user experience, and perceived usefulness of the two digital outputs.Conclusions: ePhyLi aspires to ultimately have a long-term impact on future (PE) teachers’ teaching and pedagogical practices and therefore the experience of children being taught in the future, with a subsequent impact on the currently sedentary population, as children will start to value and engage in physical activity more regularly. Also, the project will strengthen the competency profiles of HEIs staff when it comes to educating their university students in the field of PE, as well as when it comes to the use of digital tools in PE related courses.Keywords: Physical literacy, higher education, digital tools, physical education